LINK BETWEEN LIFE VALUES AND DELIBERATE SELF-REGULATION IN PEDAGOGUES: CROSS-CULTURAL ISSUES - Olga V. Bondarenko; Elena T. Bulgakova; Vladimir A. Solomonov; Oksana V. Tatarenko (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the results of a correlation study into the dominant values and deliberate self-regulation in pedagogues residing in multi-cultural (Stavropol Region, Krasnodar Region) and mono-cultural republics (Republics of North-Caucasus). The authors also present a view on the cross-cultural issues related to the interrelation detected.